EKSPLORASI LIMBAH SABUT KELAPA SEBAGAI ALTERNATIF PENDUKUNG MATERIAL RAMAH LINGKUNGAN UNTUK FURNITURE - Mahamudin, Muhammad Alif; Setiawan, Alvian Fajar; Muttaqien, Teuku Zulkarnain (Telkom University, 2024)
One part of the coconut fruit is coconut fiber which can be processed and broken down to become a product that is needed in the domestic market and even has export value. Coconut fiber also has two derivative products in the form of coconut fiber (Cocofiber) and coconut fiber powder (Cocopeat), of which the two derivative products have not yet been optimally processed to become a new material or support for a furniture product. Because the processing is not optimal, there is still a lot of coconut fiber waste that is thrown away, which can pollute the environment and cause health problems if burned. Therefore, this research was carried out to prevent these problems through exploration using qualitative methods and observation approaches and interviews with experts, as well as using the Exploring method to produce a new material or support for a sustainable and environmentally friendly furniture product (Sustainable). Keywords: Coconut fiber, cocofiber, cocopeat, exploration, sustainable